Drive-Based Behavior Modeling for Emotionally Responsive NPCs - Bicalho, Luís Fernando; Baffa, Augusto; Feijó, Bruno (Anais do Simpósio Brasileiro de Jogos e Entretenimento Digital (SBGames), 2025)
Introduction: In recent years, the development of more believable and emotionally responsive non-player characters (NPCs) has become a growing research focus. To improve immersion and behavioral realism, many models have incorporated psychological and neuroscientific theories to simulate emotion-driven decision-making. Objective: This work proposes a computational model that integrates internal needs, emotional states, and neurotransmitter simulation to create NPCs capable of dynamic, contextsensitive behavior grounded in human psychological principles. Methodology or Steps: The model draws from Hull’s drive theory, Maslow’s hierarchy of needs, and Lövheim’s Cube of Emotion. Internal variables—such as hunger, fatigue, social need, and safety—modulate neurotransmitter levels (dopamine, serotonin, noradrenaline), generating emotional states. These emotions influence behavioral transitions in an extended Finite State Machine (FSM). A prototype developed in the Godot Engine was used to simulate and evaluate the system. Results: Simulation results demonstrate that NPCs exhibit behavior consistent with psychological expectations, including appropriate emotional triggers and adaptive decision-making. The proof-of-concept highlights the potential of the model for applications in games, simulations, and narrative systems, offering a scalable foundation for emotionally intelligent agents.